Approach to gender and sexuality to promote the mental health of young women in the school contex (Research, Society and Development, 2022)
The school becomes paramount in the path of sexual and gender education, breaking paradigms and forming sensitive subjects prepared to live and live together, respecting the differences of each individual. Above all, the teacher has a fundamental role in intervening with actions aimed at building an equitable school space, aimed at promoting the mental health of young people. This study aimed to understand the importance of approaching gender and sexuality to promote the mental health of young women in the school context. This is a Narrative Review of Literature (RNL), with a descriptive/exploratory character, through a qualitative approach. It is the educator's duty to be interested and seek to understand the individuality of each student, for this it is always feasible to seek new teaching alternatives to cover the vast majority of subjects. In addition, the school needs to train professionals in terms of integrating the approach to issues such as gender, sexuality and mental health, aiming at health promotion.